Monitoração ecocardiográfica da atriosseptostomia com balão - Marchi, Carlos Henrique de (2004)
Objective: Balloon atrial septostomy (BAS) is a life-saving palliative procedure for some congenital heart defects and typically performed in the cardiac catheterization laboratory. The aim of this study was to evaluate BAS under echocardiographic guidance. Method: From August 1997 through January 2004, 31 children with congenital heart defects with indication of ASB were submitted to the procedure under exclusive echocardiographic guidance. Success was admitted the obtaining of atrial septal defect (ASD) with size of four millimeters (mm) or greater and torn septal tissue flapping freely. Results: Male infants predominated (83.9%). Median age was 5 days (1 - 150) and median weight was 3300g (1800 - 7500). Transposition of the Great Arteries was present in 80.6%, Tricuspid Atresia in 12.9%, Total Anomalous Pulmonary Venous Return in 3.2% and Pulmonary Atresia with intact ventricular septum in 3.2%. The procedure was successful in all cases. ASD size increased from 1.8 ± 0.8 mm to 5.8 ± 1.3 mm (P<0.0001) and arterial oxygen saturation increased from 64.5 ± 18.9% to 85.1 ± 9.2% (P<0.0001). As complications occured three balloon ruptures, one tear of right femoral vein, one case of supraventricular tachycardia and one case of atrial flutter. Conclusion: BAS under echocardiographic guidance is a safe and effective method. It can be performed at the bedside, identifies the catheter location avoiding serious complications and evaluates the immediate result of the procedure.